Determinants of Gender-Based Violence in Nepal: A Review of Recent Evidence - Dhital, Krishna Prasad (NPRC Journal of Multidisciplinary Research, 2025)
Background: Gender-based violence (GBV) remains a major global public health and human rights challenge, significantly impacting women’s health and well-being. In Nepal, GBV is a pervasive societal crisis, with impacts that undermine the nation’s progress. Recent evidence indicates that GBV persists at high levels, affecting women and girls across various settings, including schools and homes. Objectives: This narrative review aims to synthesize recent evidence on GBV in Nepal, with a focus on examining its determinants across multiple ecological levels—including individual, relationship, household, community, and institutional factors—to inform evidence-based prevention programs and policy interventions. Methods: This review is based on a synthesis of recent literature, including national surveys and empirical studies. The analysis is guided by a socio-ecological model, which recognizes that GBV is influenced by factors operating at multiple levels, from individual beliefs to broader societal structures. Findings: The review confirms the high prevalence of GBV in Nepal. A recent cross-sectional study among secondary school female students in the Sarlahi district found that 45.33% had experienced lifetime GBV, broken down into psychological (39.56%), sexual (30.22%), and physical violence (16.89%). Key risk factors identified include: • Individual/Relationship Level: Husband’s alcohol use and poor marital communication are significant risk factors for intimate partner violence (IPV). • Household Level: Economic stress, type of family, and gender-based discrimination within the family are associated with GBV experience. • Community & Societal Level: Patriarchal norms, gender-inequitable attitudes, and the intergenerational transmission of violence (e.g., witnessing violence as a child) are deeply entrenched drivers of GBV. Despite existing laws, services for survivors remain fragmented, and emotional abuse is often overlooked due to a lack of physical evidence. Conclusion: GBV in Nepal is a complex issue driven by interconnected factors across the socio-ecological spectrum. While physical and sexual violence are documented, psychological violence is highly prevalent yet frequently overlooked by support systems. Implication: There is an urgent need for a multi-sectoral approach to effectively prevent and respond to GBV. This should include: • Strengthening institutional frameworks and multi-sectoral response services. • Implementing community-based programs that challenge harmful gender norms and engage men and boys. Improving access to integrated services—including legal, psychosocial, and health support—for survivors, particularly in remote areas.